2007
DOI: 10.1002/ijc.22980
|View full text |Cite
|
Sign up to set email alerts
|

A novel algorithm for reliable detection of human papillomavirus in paraffin embedded head and neck cancer specimen

Abstract: Human papillomavirus type 16 (HPV16) plays a role in the development of a subgroup of head and neck squamous cell carcinomas (HNSCC). However, uncertainty exists about the true impact of HPV in this tumor type as conflicting reports have been published with prevalence rates from 0 to 100%. We aimed to find a detection algorithm of a biologically and thus clinically meaningful infection, applicable for high-throughput screening of frozen and formalin-fixed paraffin embedded (FFPE) specimens. By considering dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
756
4
14

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 666 publications
(805 citation statements)
references
References 50 publications
31
756
4
14
Order By: Relevance
“…To assess a firm association between virus and tumor cells, namely, it is recommended to carry out additional tests, such as p16 INK4A immunostaining Cell cycle protein expression and HPV in tonsillar carcinoma HC Hafkamp et al and/or FISH, which has been applied in our study. 55,56 In the univariate and multivariate statistical analyses, we found that p21 Cip1/WAF1 overexpression was a highly significant indicator of favorable prognosis in tonsillar squamous cell carcinomas independent of HPV status. Expression of p21 Cip1/WAF1 has also been associated with a favorable survival in patients with tongue squamous cell carcinomas, and in patients with ovarian, superficial bladder, gastric, colorectal, and esophageal cancers.…”
Section: Discussionmentioning
confidence: 89%
“…To assess a firm association between virus and tumor cells, namely, it is recommended to carry out additional tests, such as p16 INK4A immunostaining Cell cycle protein expression and HPV in tonsillar carcinoma HC Hafkamp et al and/or FISH, which has been applied in our study. 55,56 In the univariate and multivariate statistical analyses, we found that p21 Cip1/WAF1 overexpression was a highly significant indicator of favorable prognosis in tonsillar squamous cell carcinomas independent of HPV status. Expression of p21 Cip1/WAF1 has also been associated with a favorable survival in patients with tongue squamous cell carcinomas, and in patients with ovarian, superficial bladder, gastric, colorectal, and esophageal cancers.…”
Section: Discussionmentioning
confidence: 89%
“…This high clinical sensitivity most probably is due to targeting ultra-short RNA sequences of only 65-75 base pairs specifically amplified after random cDNA generation as first used for HPV16 by Smeets and coworkers. 29 This high sensitivity of HPV RNA detection in FFPE tissues raises the possibility to explore the value of these RNA assays even for primary HPV infection diagnosis in FFPE tissues with poor nucleic acid conservation. Assay specificity for both HPV type and RNA is enhanced by the combination of type-specific and RNA-specific oligonucleotides, the two PCR primers and the splice-site specific probe, the latter excluding false-positive detection of amplified genomic viral DNA sequences.…”
Section: Discussionmentioning
confidence: 99%
“…28 Recently, an ultra-short amplicon, E6*I mRNA RT-PCR assay has been described for HPV16. 29 Advantages of such an assay are applicability to FFPE material and absolute RNA specificity by using a splice-site as identification target.…”
mentioning
confidence: 99%
“…No single detection method seems to give reliable results on FFPE. Smeets et al 16 proposed a combination of p16 IHC followed by HPV-DNA GP51= 61 PCR on the p16-positive cases, which has recently been validated by comparing E6=E7 RT-PCR and p16 IHC=HPV-DNA PCR on both frozen and FFPE tissue samples of 82 patients, showing a concordance of 98%. 11 Other studies advocated a triple method using p16 IHC, HPV-DNA PCR and HPV ISH 17 or p16 IHC and histological evaluation of basaloid differentiation.…”
Section: Discussionmentioning
confidence: 99%